Razlikovanje med upravnimi in delovnopravnimi zadevami v postopkih pravnega varstva javnih uslužbencev - Štemberger Brizani, Katja (Delavci in delodajalci, 2024)
Based on the theoretical premises and case law, the paper critically analyses the legal regulation of the legal protection of civil servants, which is divided into administrative and labour law protection, depending on the form of the act, subject to legal protection. It notes that the Public Employees Act does not consistently apply the formal criterion, according to which a matter is presumed to be an administrative matter if a regulation provides for the issuance of an administrative decision, but also provides for legal protection in the administrative sphere against orders and notices, which indicates that these matters are also administrative matters. In addition to the formal criterion, the substantive criterion must also be applied. According to the latter, an administrative matter – irrespective of the designation of the act – is examined (determined) on its merits. To avoid legal confusion caused in practice by inconsistent terminology and opaque statutory provisions, the legislator should define administrative matters more precisely, either by consistently using the term 'administrative decision' or by listing the matters classified as administrative matters taxatively (following the example of the Croatian legislation). However, in any case, the substantive criterion should also be applied (complementary).
Keywords: act of political discretion; administrative matter; javna uprava; javni uslužbenci; labour law matter; legal protection; pravno varstvo; Zakon o javnih uslužbencih